Hidrólisis de la urea y del biuret en algunos suelos de Costa Rica - Acevedo, A.; Pereira, J.F. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The hydrolysis of urea and biuret in ten soils from Costa Rica was studied by chemical analysis of the ammonium and nitrate fractions. The percentage of ammonium produced during the hydrolysis of urea reached the apparent highest value two days after the application of urea to the soil, but later it decreased directly proportional to time and for the percentage of ammonium to become less than ten per cent of the initial nitrogen applied as urea, it took from 9 to 29 days, depending on each particular soil. Since it is considered that nitrate is formed from ammonium, the nitrate fractions always showed a straight up tendency, although during the experimental period, did not reached the 100% of the total nitrogen applied to the soils. The biuret hydrolysis was a slower process than that of urea, and the ammonium produced seemed to be oxidized quickly in some soils, since the quantity of ammonium nitrogen never was bigger than 4.1% of the total applied. The rate of nitrate formation was dependable of each particular soil